2007
DOI: 10.1590/s0102-05362007000400009
|View full text |Cite
|
Sign up to set email alerts
|

Produção de melão Cantaloupe influenciado por coberturas do solo, agrotêxtil e lâminas de irrigação

Abstract: Melon yield and fruit quality as influenced by soil coverages, agrotextile and irrigation depth in dry seasonTwo experiments were carried out at the same time in Baraúna, Rio Grande do Norte State, Brazil, from October to December 2004, to evaluate different soil coverages and irrigation depth as well as the use of agrotextile on the melon yield. In the first experiment the agrotextile was used, but not in the second one. Both experiments were designed in a 5 x 3 factorial scheme in randomized complete blocks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
20

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 3 publications
1
12
0
20
Order By: Relevance
“…Crusier with TNT protection up to 10, 20 and 32 days after planting (DAP) resulted in earlier plants with higher marketable and total yields compared to the control, without the protection. In Baraúna, Rio Grande do Norte state, Medeiros et al (2007), keeping the Cantaloupe melon 'Torreon' protected with TNT up to 28 DAT verified a significant increase of 16.43% and 12.96%, respectively, in the number of total and marketable fruits. The different productive performance of the Cantaloupe melon protected temporarily with TNT in different regions, including this study, can be explained by the genotype x environment interaction.…”
Section: Pdatmentioning
confidence: 95%
See 1 more Smart Citation
“…Crusier with TNT protection up to 10, 20 and 32 days after planting (DAP) resulted in earlier plants with higher marketable and total yields compared to the control, without the protection. In Baraúna, Rio Grande do Norte state, Medeiros et al (2007), keeping the Cantaloupe melon 'Torreon' protected with TNT up to 28 DAT verified a significant increase of 16.43% and 12.96%, respectively, in the number of total and marketable fruits. The different productive performance of the Cantaloupe melon protected temporarily with TNT in different regions, including this study, can be explained by the genotype x environment interaction.…”
Section: Pdatmentioning
confidence: 95%
“…In Brazil, some studies have shown the importance of knowledge about the growth and physiological indices as well as the influence of agronomic practices and external factors on the final production of the plant (Medeiros et al, 2006(Medeiros et al, , 2007Morais et al, 2008), however studies related to this subject about the delay of removing the row cover, as a resource to change the source-drain ratios in melon production, are not common.…”
Section: Palavras-chavementioning
confidence: 99%
“…The necessary condition for success in growing this plant is directly related to high luminosity, temperature, low rainfall and low relative humidity (Medeiros et al, 2007). These weather conditions are found in Sertão Region of the State of Paraíba, however, due to low level of technology and inappropriate plant management adopted by small producers, the production has been low.…”
Section: Scientific Communicationmentioning
confidence: 99%
“…Embora os filmes plásticos de polietileno sejam amplamente utilizados como mulching em diversas hortaliças, o tecido de polipropileno ou agrotêxtil (TNT) tem sido empregado como manta sobre as plantas de melão e melancia (Medeiros et al, 2007;Dantas et al, 2009) mas também, recentemente como cobertura do solo, proporcionando aumento de produção e diminuindo a incidência de plantas daninhas, em hortaliças como a alface (Reghin et al, 2002) e maior produtividade de frutos comerciais no cultivo do tomate (Factor et al, 2009).…”
unclassified